The Role of Muhammadiyah in the Development of Progressive Islamic Education in Indonesia: A Study of the Educational Enterprises of the Al Ikhlas Islamic Boarding School in Tolobali, Bima City - Baharuddin Baharuddin; Adam Adam; Nur Itam; Ihlas Ihlas; Hendra Hendra (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to analyze the role of Muhammadiyah in the development of progressive Islamic education and identify the challenges faced in its implementation at the Al Ikhlas Tolobali Islamic Boarding School in Bima City. The focus of the study is directed at aspects of educational institutional development, educational programs, integration of religious knowledge and general knowledge, and educational management. This study uses a qualitative approach with a descriptive qualitative research type. Data were collected through observation, interviews and documentation. Data analysis is based on three steps: data reduction, data presentation, and conclusion drawing, while data validity is through member check, cross check, and method triangulation techniques. The results of the study indicate that Muhammadiyah plays a significant role in the development of progressive Islamic education at the Al-Ikhlas Tolobali Islamic Boarding School in Bima City through strengthening tiered educational institutions, developing superior programs such as Tahfidzul Qur'an and santri entrepreneurship, integrating religious knowledge and general knowledge in the curriculum, and implementing more modern and transparent educational management. The challenges faced are limited human resources, low utilization of learning technology, and limited supporting facilities and infrastructure. These findings emphasize the need for strategies to strengthen human resources, technology-based learning innovations, and support facilities to optimally realize progressive Islamic education.